Analysis of serum gastrin‐17 and Helicobacter pylori antibody in healthy Chinese population. Issue 12 (30th August 2020) - Liu, Wenjun; Sun, Youxiang; Yuan, Yulin
Abstract: Background: Gastrin‐17 (G‐17) and Helicobacter pylori ( H pylori ) antibody are widely used in the screening of gastric diseases, especially in gastric cancer. In this study, we aimed to evaluate the value of G‐17 and H pylori antibody in gastric disease screening. Methods: Healthy males and females (1368 and 1212, respectively) aged between 21‐80 years were recruited for the study. Serum G‐17 value was measured using ELISA, and H pylori antibodies were measured using Western blotting. Statistical analyses were performed using the chi‐square, Mann‐Whitney U, and Kruskal‐Wallis H tests. Results: Serum G‐17 level was higher in the H pylori‐ positive group than in the negative group. Serum G‐17 level was higher in the type 1 H pylori‐ positive group than in the type 2 H pylori‐ positive group. Further, serum G‐17 level was higher in females than in males and showed significant differences among different age‐groups, with changes in trend proportional to the age. The positive rate of H pylori infection in all the subjects was 58.29% and did not show a significant difference between males and females. However, it showed significant differences among different age‐groups, with the changing trend proportional to the age. Conclusion: Analysis of serum G‐17 level and H pylori antibody typing is valuable in gastric disease screening. Every laboratory should establish its own reference interval for G‐17 level. Abstract : Serum G‐17 level was higher in females than in males, and the changing trend of serum G‐17 level was proportional to age.